2016
DOI: 10.1109/jlt.2015.2482718
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the Soft-Decision FEC Limit Paradigm in the Design of Optical Communication Systems

Abstract: Abstract-The FEC limit paradigm is the prevalent practice for designing optical communication systems to attain a certain bit-error rate (BER) without forward error correction (FEC). This practice assumes that there is an FEC code that will reduce the BER after decoding to the desired level. In this paper, we challenge this practice and show that the concept of a channel-independent FEC limit is invalid for soft-decision bitwise decoding. It is shown that for low code rates and high order modulation formats, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(25 citation statements)
references
References 58 publications
0
22
0
3
Order By: Relevance
“…Moreover, the enhancement on the flexibility of transmission capacity indicates that PS bit loading technology is a more suitable and robust modulation method to take advantage of the channel capacity in the UVC solar-blind communication system with complex frequency-fading issues. We also observed that the NGMI values for all subcarriers are above 0.9 (allowing the use of a rate-0.858 FEC code), which means that using the concatenated code of 20% low-density parity-check (LDPC) and 6.25% staircase code as the FEC code can provide error-free transmission and achieve 10 −15 post-FEC BER [29]. The FEC code redundancy can be reduced even further using a binary rate-0.9 FEC code if it is developed in the future.…”
Section: Angle Of Viewmentioning
confidence: 82%
“…Moreover, the enhancement on the flexibility of transmission capacity indicates that PS bit loading technology is a more suitable and robust modulation method to take advantage of the channel capacity in the UVC solar-blind communication system with complex frequency-fading issues. We also observed that the NGMI values for all subcarriers are above 0.9 (allowing the use of a rate-0.858 FEC code), which means that using the concatenated code of 20% low-density parity-check (LDPC) and 6.25% staircase code as the FEC code can provide error-free transmission and achieve 10 −15 post-FEC BER [29]. The FEC code redundancy can be reduced even further using a binary rate-0.9 FEC code if it is developed in the future.…”
Section: Angle Of Viewmentioning
confidence: 82%
“…21. As a figure of merit, besides the pre FEC BER, we use the normalized generalized mutual information (NGMI), as it has been shown to provide consistent post FEC BER predictions across different conditions and modulation formats [23]. Considering the FEC overhead for LDPC codes concatenated with a staircase code [24], the NGMI of 0.88 and 0.92 shown in this figure corresponds to a overall rate of 0.81 and 0.85 respectively, meaning that for the gross data-rate of 199.80 Gb/s the net data-rates after FEC decoding will be 161.84 Gb/s and 169.83 Gb/s for the NGMI values of 0.88 and 0.92 respectively.…”
Section: Coherent Experimental Resultsmentioning
confidence: 99%
“…10a. Note that generalized mutual information (GMI) 28 is used for accurately measuring the gain of NN-NLC for PS-64QAM format. Figure 10c compares the performance of NN-NLC and filtered-DBP with respect to the CDC only as a function of computation complexity.…”
Section: Resultsmentioning
confidence: 99%